Application of Geographic Information System For Irrigation Management - J., Deepak T. (2002)
Water plays an important role in crop production. A good irrigation water management system has to be provided to give adequate and timely supply of water to improve the crop production. In order to achieve this, it is necessary to have adequate water source, a good conveyance system, a good distribution system and a strong database to store all the required data. Improved management can be achieved when the study area has been provided with a good database to store the real time data according to the seasons that will help the users and the decision makers to make a firm decision with respect to the management aspect. Visual Basic and GIS can greatly help to achieve efficient water management. The Tanjung Karang Rice Irrigation Project in Northwest Selangor Malaysia was selected for this study and three compartments Sawah Sempadan, Sungai Burong and Sungai Nipah were considered for the study. The Visual Basic program designed in this study with several screens provides unique results based on the water management. The program was designed, tested and the results stored in MS-Access database. This study concentrates on creating an irrigation water management database and providing a user-friendly on-farm decision support system to benefit the farmers and the farm managers. Critical solutions can be achieved by creating a useful database for irrigation management. The designed database can store, edit, update and delete the data records whenever necessary. The GIS user interface for the irrigation system promIses to provide comprehensible results to improve the decision making process in the operation and management of the scheme. MapInfo Professional Software 5.0 was used to digitize the Tanjung Karang study area. The digitized maps were exported from MapInfo to ArcView GIS 3.1 using Universal Translator. ArcView GIS 3.1 was used for analysis and the results shown in the form of thematic maps, tables, graphs and charts to benefit the users and decision makers involve with irrigation water management.